2014
DOI: 10.1186/1471-2458-14-643
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic studies of modifiable factors associated with cognition and dementia: systematic review and meta-analysis

Abstract: BackgroundCognitive impairment, including dementia, is a major health concern with the increasing aging population. Preventive measures to delay cognitive decline are of utmost importance. Alzheimer’s disease (AD) is the most frequent cause of dementia, increasing in prevalence from <1% below the age of 60 years to >40% above 85 years of age.MethodsWe systematically reviewed selected modifiable factors such as education, smoking, alcohol, physical activity, caffeine, antioxidants, homocysteine (Hcy), n-3 fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
444
8
28

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(511 citation statements)
references
References 303 publications
(467 reference statements)
31
444
8
28
Order By: Relevance
“…These findings are consistent with previous community studies showing an association between odour identification scores and decline on a general cognitive functioning measure [12,36]. The reason that we only found an association with the MMSE may be explained by the fact that the MMSE does not have a floor effect in mild-moderate dementia and is perhaps less vulnerable to practice effects as opposed to cognitive tests.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are consistent with previous community studies showing an association between odour identification scores and decline on a general cognitive functioning measure [12,36]. The reason that we only found an association with the MMSE may be explained by the fact that the MMSE does not have a floor effect in mild-moderate dementia and is perhaps less vulnerable to practice effects as opposed to cognitive tests.…”
Section: Discussionsupporting
confidence: 82%
“…Also, in our study no association between CSF markers and semantic memory was found, but these results were just above threshold of statistical significance. In addition, we found that the association between CSF markers and memory performance was similar across diagnostic groups, while other studies reported that some of the associations between CSF markers and memory performance were observed in specific diagnostic groups only [15,36,37]. These differences may be explained by the statistical approach.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Angel, Fay, Bouazzaoui, Baudouin, and Isingrini (2010) refer to the interaction between age and education in performing a wordlist recalling task, in which adults with lower levels of education performed poorly when compared with those with higher levels of formal education. Although it is expected that some cognitive skills decline with age, some changes are clearly associated with education (Beydoun et al, 2014). Foss, Formigheri and Speciali (2009), for example, find significant positive correlations between level of education and performance in VEM tests in the elderly.…”
mentioning
confidence: 99%
“…The emerging role of homocysteine in predicting cognitive decline independent of cardiovascular risks has drawn equal attention in the context of cognitive aging and AD [12][13][14][15][16][17]. In the seminal Framingham study recruiting 1092 normal healthy subjects (677 female and 425 male; mean age: 76 years) were followed for 8 years for repeated plasma Hcy monitoring [13].…”
Section: Introductionmentioning
confidence: 99%